Derivation of Moments during a Busy Period - Fan, Rocky Yuk-keung (My University, 1987)
The purpose of this project is to derive the first two moments of two random variables, that is, the number served during and the length of a busy period. Two singleserver models are discussed in this project, namely, the Mb°∕Ea∕ 1 model, and the Mb∕Mb∕1 model. Moreover, in the development, standard methods such as the moment generating function technique are used, application of a computer system will also be introduced.
Keywords: Queueing theory; statistics